Incidental Vocabulary Learning and Retention in Education-oriented L2 Communicative Tasks - Aitor Garcés-Manzanera (Miscelánea: A Journal of English and American Studies, 2023)
Vocabulary learning is pivotal for language learning as it is a cross-sectional aspect related to both receptive and productive skills. L2 vocabulary learning has given way to a substantial body of research in which the role of implicit and explicit instruction has been central. Bearing in mind the importance of communicative tasks as sources for vocabulary learning, this study will explore how vocabulary presented with context and without context is retained. 39 undergraduate students were assigned to each of these conditions, and after performing a communicative task which included a warm-up activity with a set of 15 target words, they completed a word meaning test (post-test) and repeated the same test after two weeks. The data gathered was analyzed using a quantitative approach. Findings indicate that the type of vocabulary test with context-embedded words is more effective for vocabulary retention in the short term. Nevertheless, multi-word items were better identified with the no-context vocabulary test, a finding supported by previous research. The present study raises the possibility that different vocabulary strategies are used by EFL learners, and that warm-up activities may contribute to L2 vocabulary learning.